Globalization, trade reform, and the developing countries: essay in IFPRI Annual Report - Díaz-Bonilla, Eugenio; Robinson, Sherman (International Food Policy Research Institute, 1999)
This essay focuses on trends reflecting the globalization of the international economy and on changes in agricultural markets. In this context it assesses how these factors are affecting developing countries and how, in turn, those countries could affect the Millenium Round of agricultural trade agreements,